Crosstalk between gut microbiota dysbiosis and mercury-induced hepatointestinal toxicity in mice - Siyu Li; Biqi Han; Jiayi Li; Zhanjun Lv; Yunfeng Liu; Ruifeng Gao; Zhigang Zhang (Environmental Pollution, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Synthesis of monolithic beta zeolite composed of ultra-small nanocrystals and its application in toluene adsorption - Jiahui Zhang; Chuyu Jiao; Qihao Wu; Zhongxu Wang; Yi Liu; Jiajun Zheng; Weijiong Dai; Yan Wang; Lei Han; Wenlin Li; Ruifeng Li (Journal of Environmental Chemical Engineering, 2026)

Temporal trajectory and determinants of permanent gully erosion in the grassland: A long-term analysis spanning 1973–2020 - Zhicai Xiao; Mingming Guo; Xin Liu; Zhuoxin Chen; Xingyi Zhang; Jinzhong Xu; Shaoliang Zhang; Jielin Liu; Xing Han; Ruifeng Xie (Soil and Tillage Research, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Elucidating the influence of Lactobacillus plantarum 21802 on nutritional and flavor profiles of peach purees from different flesh-colored peach cultivars - Qiaoyu Han; Jiechao Liu; Ruifeng Wang; Hui Liu; Qiang Zhang; Zhenzhen Lv; Dalei Chen; Wenbo Yang; Zhonggao Jiao (Food Bioscience, 2026)

Noise Characteristics and Shallow Subsurface Structure Detection in Coastal Zones: A Case Study from Dong’ao Island, Zhuhai - Siqing Liu; Sixu Han; Yongzhi Liang; Shuji Yang; Yi Chai; Tongying Hu; Ruifeng Wu; Yu Li; Qingxian Zhao; Zengjia Li; Wei Zhang; Xianqing Wang; et al. (Journal of Marine Science and Engineering, 2026)
Shallow subsurface structure detection in coastal zones serves as a critical foundation for resource development and engineering construction. However, conventional geophysical methods exhibit significant limitations in land–sea transition zones, where pronounced “boundary effects” create substantial “exploration gaps” due to difficulties in merging terrestrial and marine datasets. To achieve truly seamless subsurface imaging across the coastal boundary, this study develops and implements an integrated cross-boundary survey approach utilizing nodal seismometers and seismic ambient noise. At Dong’ao Island, Zhuhai, we deployed a comprehensive seismic profile spanning hillside, sandbeach, and seafloor environments to evaluate the method’s applicability in complex coastal settings systematically. Results demonstrate substantially stronger ambient noise energy in submarine environments compared to terrestrial settings. All stations recorded abundant and stable high-frequency (>1 Hz) noise signals, which are adequate for shallow subsurface imaging. Rayleigh wave dispersion curves extracted via the advanced Frequency-Bessel transform method enabled inversion of a continuous 2D shear-wave velocity profile along the survey line. Bedrock interface depths determined using the Horizontal-to-Vertical Spectral Ratio (HVSR) method showed remarkable consistency with the bedrock morphology revealed by the shear-wave velocity structure, validating the reliability of our approach in coastal environments. This research successfully demonstrates the feasibility of seismic ambient noise imaging as a bridging technique for land–sea exploration, providing an efficient, environmentally friendly, and continuous technical solution to overcome coastal zone exploration challenges.

Evaluation of cropland utilization efficiency and analysis of risk mechanisms under abandonment patterns in the Guanzhong region - Tong Zhou; Ruifeng Zhao; Quanlin Ma; Lihua Zhang; Fushou Liu; Pengbin Bao; Jingfa Wang; Ziyi Han; Xiaonuo Guo (Journal of Environmental Management, 2026)

How does cultural values influence public willingness to protect wetlands? — Take Tibetan cultural values as an example - Ziyi Han; Ruifeng Zhao; Lihua Zhang; Siyu Ming; Xidong Chen; Jingfa Wang (Journal of Environmental Management, 2025)

The threat of PPCPs from WWTP and solutions of advanced reduction coupled treatment processes with pilot-scale - Ruifeng Yan; Jinglong Han; Guti Shen; Zhineng Hao; Yingnan Han; Wei Xiong; Bin Liang; Shuhong Gao; Min Yang; Yilu Sun; Changmin Wu; Jifang Zhang; et al. (Journal of Hazardous Materials, 2025)

Statistical analysis of the spatio-temporal characteristics of multiple return strokes cloud-to-ground lightning parameters in Guangdong Province, China - Zhiming Liao; Yongxia Han; Licheng Li; Yuanzhi Wu; Fei Yu; Qian Li; Ruifeng Zhu; Zhenxin Zhong (Atmospheric Research, 2025)

Recent marine carbonate hardgrounds at Abu Dhabi: towards a better understanding of ‘hidden hardgrounds’ in the geological past - Chao Chen; Hanting Zhong; Xia Wang; Meng Ning; Xinyu Wang; Han Wang; Ruifeng Tang; Mingcai Hou (Frontiers in Marine Science, 2025)
Marine hardgrounds are common features during the Phanerozoic and hold significant sedimentological and economic importance. Intriguingly, previous reports of marine hardgrounds are concentrated in Calcite Seas, despite elevated seawater CaCO 3 saturation in Aragonite Seas. This bias remains unclear in origin and requires more hardground information, especially from Aragonite Seas, for clarification. Well-developed Holocene marine hardgrounds at Abu Dhabi provide such a good opportunity. This study focused on a widespread and well-developed Holocene marine hardground layer at Abu Dhabi and analyzed its chronostratigraphy, petrology, mineralogy, and geochemistry. The results show that the studied hardground layer can be divided into lower and upper parts, characterized by planar upper surface and no borings nor encrustations. The lower part (with a 14 C age of 6945−6368 cal yrs BP) formed during a sea-level transgression, and is laterally traceable along both a seaward and a landward direction. The upper part (with a 14 C age of 5871−5452 cal yrs BP) formed during following sea-level transgression and/or stillstand, and disappears along a landward direction. Compared with the lower part, the upper hardground part is higher in δ 13 C carb and δ 18 O carb , supporting formation within more evaporated seawater settings depositing more high-Mg calcite. Both parts consist mainly of aragonite and high-Mg calcite in both carbonate grains and intergranular early-marine cement, but the lower hardground part contains more protodolomite within the early-marine cement. Moreover, an inverse relation in contents indicates a diagenetic transition from aragonite to dolomite during hardground formation and early diagenesis. Further, in combination with previous studies, the findings of this study confirm the rapidity, lateral diachronicity, and composite nature of Holocene marine hardgrounds with mineralogy controlled by sea-level changes. Similar hardgrounds may also be well developed in ancient records (especially in Aragonite Seas like the modern ocean), but be ignored due to lack of recognizable features (e.g., boring, irregular upper surfaces, Fe-Mn encrustation) and mineral recrystallization. These “hidden hardgrounds” and their composite formation by diachronous parts have implications for sequence stratigraphy and hydrocarbon exploration using hardgrounds in stratigraphic correlation.

Plant life form determines net ecosystem CO2 exchange in a salt marsh under precipitation changes - Zhenghao Liang; Jia Song; Xinge Li; Mingliang Zhao; Xiaojing Chu; Xiaojie Wang; Peiguang Li; Xiaoshuai Zhang; Weimin Song; Siyu Wei; Ruifeng Sun; Changsheng Jiang; et al. (Agricultural and Forest Meteorology, 2025)

Warming‐Induced Plant Species Shifts Lead to Substantial Losses of Wetland Soil Carbon - Baoyu Sun; Ruifeng Sun; Jianjun Xu; Wenjing Gao; Xiaojing Chu; Huilan Yuan; Fangxiu Wan; Liming Yan; Guangxuan Han; Jianyang Xia; Ming Nie (Ecology Letters, 2025)
Wetlands are large reservoirs of soil organic carbon (SOC), storing one‐third of global SOC within 6% of the land surface. However, the feedback direction and magnitude of wetland SOC storage to climate warming remain unclear. Here we present results from an 8‐year (2014–2022) wetland warming experiment in the Yellow River Delta, revealing that wetland SOC storage responds to warming in a phase‐dependent manner. We found that warming initially reduced both carbon input and output but did not change SOC storage. However, SOC storage abruptly decreased by 21.4% in 2020, which persisted over the following 2 years. This occurred mainly due to shifts in the biomass of dominant plant species ( P. australis ) under warming, reducing carbon input, increasing microbial carbon degradation, and resulting in microbial necromass carbon loss. These results highlight the critical role of dominant plant species in driving the wetland soil carbon cycle and its feedback to climate change.

Experimental study on direct contact condensation of steam bubbles with non-condensable gas at high Reynolds numbers - Taikun Guo; Junying Hong; Rui Han; Ruifeng Tian; Sichao Tan; Jiming Wen (Annals of Nuclear Energy, 2025)

Weights embedding Informer prediction algorithm-based fault diagnosis framework for nuclear power plant - Tan Canyi; Zheng Wei; Wang Bo; Tan Sichao; Liang Biao; Li Jiangkuan; Han Rui; Ke Zhiwu; Tian Ruifeng (Annals of Nuclear Energy, 2024)

Gain-of-function variants in GSDME cause pyroptosis and apoptosis associated with post-lingual hearing loss - Yun Xiao; Lei Chen; Kaifan Xu; Meijuan Zhou; Yuechen Han; Jianfen Luo; Yu Ai; Mingming Wang; Yu Jin; Ruifeng Qiao; Shuhui Kong; Zhaomin Fan; et al. (Human Genetics, 2024)
Gasdermin E (GSDME), a member of the gasdermin protein family, is associated with post-lingual hearing loss. All GSDME pathogenic mutations lead to skipping exon 8; however, the molecular mechanisms underlying hearing loss caused by GSDME mutants remain unclear. GSDME was recently identified as one of the mediators of programmed cell death, including apoptosis and pyroptosis. Therefore, in this study, we injected mice with GSDME mutant (MT) and examined the expression levels to assess its effect on hearing impairment. We observed loss of hair cells in the organ of Corti and spiral ganglion neurons. Further, the N-terminal release from the GSDME mutant in HEI-OC1 cells caused pyroptosis, characterized by cell swelling and rupture of the plasma membrane, releasing lactate dehydrogenase and cytokines such as interleukin-1β. We also observed that the N-terminal release from GSDME mutants could permeabilize the mitochondrial membrane, releasing cytochromes and activating the mitochondrial apoptotic pathway, thereby generating possible positive feedback on the cleavage of GSDME. Furthermore, we found that treatment with disulfiram or dimethyl fumarate might inhibit pyroptosis and apoptosis by inhibiting the release of GSDME-N from GSDME mutants. In conclusion, this study elucidated the molecular mechanism associated with hearing loss caused by GSDME gene mutations, offering novel insights for potential treatment strategies.

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

Insight into differences in whey proteome from human and eight dairy animal species for formula humanization - Zhongyuan Ji; Ruifeng Dong; Qijing Du; Hongning Jiang; Rongbo Fan; Dengpan Bu; Jun Wang; Zhongna Yu; Rongwei Han; Yongxin Yang (Food Chemistry, 2024)

Spatial-temporal evolution mechanism and dynamic simulation of the urban resilience system of the Guangdong-Hong Kong-Macao Greater Bay Area in China - Huihui Wang; Hanyu Xue; Wanlin He; Qiuyuan Han; Tingting Xu; Xiaoyong Gao; Suru Liu; Ruifeng Jiang; Mengxing Huang (Environmental Impact Assessment Review, 2024)

Seven-year experimental warming decreases labile but not recalcitrant soil organic carbon fractions in a coastal wetland - Ruifeng Sun; Baoyu Sun; Xinge Li; Siyu Wei; Mingliang Zhao; Xiaojing Chu; Weimin Song; Junji Yuan; Guangxuan Han (Journal of Soils and Sediments, 2023)

Cenozoic tectonostratigraphy and structural styles in the Nangong Sag, Bohai Bay Basin, eastern China: Implications for the generation of oil-gas traps - Tianshun Liu; Wenlong Ding; Ruifeng Zhang; Jingtian Li; Guangye Feng; Pengyuan Han; Xu Zhou; Dashuai Ye; Ziyou Zhang (Marine and Petroleum Geology, 2023)

Exogenous pyruvate and recombinant human basic fibroblast growth factor maintain pluripotency and enhance global metabolic activity of bovine embryonic stem cells grown on low-density feeder layers - Wenqiang Xu; Jing Wang; Wei Li; Lingna Gao; Ruifeng Hao; Xuejie Han; Chen Li; Hui Zhang; Xueling Li (Theriogenology, 2023)

Layered application of phosphate fertilizer increased winter wheat yield by promoting root proliferation and phosphorus accumulation - Changhong Liu; Henghui Yan; Weiyan Wang; Ruifeng Han; Zhenyan Li; Xiang Lin; Dong Wang (Soil and Tillage Research, 2023)

Evaluating water resource carrying capacity using the deep learning method: a case study of Yunnan, Southwest China - Han Zhang; Cheng Huang; Xudong Hu; Hongbo Mei; Ruifeng Hu (Environmental Science and Pollution Research, 2022)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Genesis and implications of the composition and sedimentary structure of fine-grained carbonate rocks in the Shulu sag - Xiangxin Kong; Zaixing Jiang; Chao Han; Lijing Zheng; Yiming Zhang; Ruifeng Zhang; Jianzhang Tian (Journal of Earth Science, 2017)

Down-regulation of nitrogen/carbon metabolism coupled with coordinative hormone modulation contributes to developmental inhibition of the maize ear under nitrogen limitation - Jiaojiao Yu; Jienan Han; Ruifeng Wang; Xuexian Li (Planta, 2016)

Role of lenticels and microcracks on susceptibility of apple fruit to Botryosphaeria dothidea - Yeqing Guan; Ruifeng Chang; Guojian Liu; Yi Wang; Ting Wu; Zhenhai Han; Xinzhong Zhang (European Journal of Plant Pathology, 2015)